Dihydroartemisinin is a Hypoxia-Active Anti-Cancer Drug in Colorectal Carcinoma Cells - Ontikatze, Teona; Rudner, Justine; Handrick, René; Belka, Claus; Jendrossek, Verena (Frontiers in Oncology, 2014)
Tumor hypoxia is one main biological factor that drives resistance to chemotherapy and radiotherapy. To develop a novel strategy for overcoming hypoxia-induced therapy resistance we examined the antineoplastic activity of the reactive oxygen donor Dihydroartemisinin (DHA) in human colon cancer cell lines in normoxia and severe hypoxia. In addition, we analyzed the involvement of the intrinsic apoptosis pathway for DHA-mediated cytotoxicity in HCT116 cells in short-term and long-term in vitro assays. When applied at lower concentrations (≤ 25 µM), DHA induced apoptosis in Colo205, HCT15 and HCT116 cells, whereas necrotic cell death was increased when cells were treated with higher DHA concentrations (50 µM). However, no preference for DHA-induced apoptosis or necrosis could be detected between the treatment under normoxic or hypoxic conditions. Moreover, DHA potently reduced clonogenic survival of HCT116 cells in normoxia and hypoxia. Treatment of HCT116 cells with 25 µM DHA resulted in activation of Bax under normoxic and hypoxic conditions. Interestingly, cytochrome C release from the mitochondria and caspase activation were only observed only under normoxic conditions, whereas, under hypoxic conditions DHA induced a caspase-independent apoptosis-like cell death. However, under both conditions, generation of reactive oxygen species were important mediators of DHA-induced toxicity. Further molecular analysis suggests that DHA-mediated cell death involves different sets of pro-apoptotic Bcl-2 family members. The pronounced cytotoxic activity of DHA in severe hypoxia as well as normoxia offers new perspectives for targeting the hypoxic tumor cell fraction to improve treatment outcome for cancer patients.